Heterogeneous Indicators of Cognitive Performance and Performance Variability Across the Lifespan - Rutter, Lauren A.; Vahia, Ipsit V.; Forester, Brent P.; Ressler, Kerry J.; Germine, Laura (Frontiers in Aging Neuroscience, 2020)
Reaction time and reaction time variability are core components of cognitive performance that can be captured through brief and easy-to-administer tasks of simple reaction time (Simple RT) and choice reaction time (Choice RT). The current study aims to describe age-related differences in cognitive performance, towards better characterizing normative performance across the lifespan. We examined mean and variability of response times on a Simple RT and Choice RT tasks in a large and diverse web-based sample (10,060 visitors to TestMyBrain.org). We also examined lifespan-related differences in response time variability using multiple different approaches (raw variability, mean scaled variability, and mean residualized variability). These analyses revealed significant heterogeneity in the patterns of age-related differences in performance, across metrics and within different estimates of the same metric. Based on segmented regression analysis, age of peak performance differed significantly across metrics, with young adults having the best performance based on measures of median reaction time, middle age adults at peak on certain measures of reaction time variability (standard deviation and coefficient of variability), and older adults showing the best performance based on accuracy and mean-corrected reaction time variability. Our results indicate that no single measure of cognitive performance and performance variability produces the same findings with respect to age related change, with further work needed to establish the validity of particular metrics for different applications.